Prove that, if 1 + 3x^2 + x^3 < (1+x)^3, then x>0

(1+x)^3 = x^3 + 3x^2 + 3x + 1 (Can be calculated straight away by binomial method or by multiplying brackets individually)
if (1+x)^3 > 1 + 3x^2 + x^3then: x^3 + 3x^2 + 3x + 1 > 1 + 3x^2 + x^3 3x > 0 x > 0

Answered by Vigneswaran T. Maths tutor

14554 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given that x=ln(t) and y=4t^3,a) find an expression for dy/dx, b)and the value of t when d2y/dx2 =0.48. Give your answer to 2 decimal place.


How to find the reciprocal of a graph, such as y=cos(x)?


Express 21/root7 in the form k root7.


Solve x^3+2*x^2-5*x-6=0


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences